Analysis of Factors that Affect the Understanding of MSME Players in Preparing Financial Reports - Astriwati, Astriwati; Arifin, Arifin; Tambunan, Rince; Nur, Muh (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine and analyze the effect of education level, educational background, business size, as well as the provision of information and socialization on the understanding of Micro, Small and Medium Enterprises (MSMEs) actors in preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in Kendari City. The population of this study includes all small businesses registered at the Office of Trade, Cooperatives, and MSMEs in Abeli District and West Kendari District. The sample was determined using the Slovin's formula, resulting in a total sample of 76 MSMEs. This research uses a quantitative approach, with primary and secondary data as the data source. Data analysis was conducted through classical assumption tests and multiple linear regressions. The coefficient of determination, F test, and T test were used to test the research hypothesis. The results showed that the level of education, educational background, and business size have a positive and significant influence on the understanding of MSME actors in preparing financial reports based on SAK EMKM. Meanwhile, the provision of information and socialization does not have a significant influence on the understanding of MSME actors in the same regard.